INJURIES SUSTAINED ON A DANGEROUS SIDEWALK: MUNICIPALITIES BEWARE! Dawn Pook v Nelson Mandela Bay Municipality and Emfuleni Resorts (Pty) Ltd Case no 3697/06 (SEC) - Johan Scott (Obiter, 2022)
Eight years have elapsed since the last so-called “municipality” case of note, Cape Town Municipality v Bakkerud (2000 3 SA 1049 (SCA)), was reported in our law reports. In that case we find a helpful summary of the approach of our courts to the issue of determining wrongfulness when municipalities face legal action due to injuries sustained by members of public caused by defects in the surface of sidewalks or roads under the control of such municipalities. This topic usually raises its head in the context of the application of the omissio per commissionem rule as a determinant of the possible wrongfulness of an omission which gives rise to harm on the part ofa plaintiff. It is now well established that prior conduct of the defendant, creating a potentially dangerous situation, is merely one of the considerations – albeit an important one – to be taken into account when assessing whether the defendant’s failure to take steps to protect another from suffering harm in the event of the danger materialising into causing detriment to such other person is to be regarded as a mere omission, entailing no delictual liability, or an actionable omission. In the context of the possible civil liability of a municipality for injuries sustained by someone through a defect in a road or sidewalk surface, this expression of the importance of the prior conduct factor may, however, be misleading. Nobody will deny that the building of a road or sidewalk can be depicted as prior conduct on the part of a road-building authority in respect of damage suffered at a later stage by someone who uses such facility which has deteriorated into a state of disrepair (serious or slight); however, it is now well established that the mere existence of prior conduct of some sort on its own will not necessarily point towards the existence of a duty on the part of the municipal authority tomaintain its roads and thoroughfares in immaculate condition. The boni mores or “legal convictions of the community” play an additional role in determining whether the omission in question is wrongful. Marais JA expressed himself as follows on this aspect in Cape Town Municipality v Bakkerud (supra 1056G): “When it should be adjudged that such a demand [viz that the omission oughtto be regarded as unlawful] exists cannot be the subject of any general rule; it will depend on the facts of the particular case.”Here the boni mores test will always be applied as a “supplementary criterion” for purposes of refinement. It is probably an over-simplification to make a blanket statement that a “person acts prima facie wrongfully when he creates a new source of danger bymeans of positive conduct (commissio) and subsequently fails to eliminate that danger (omissio), with the result that harm is caused to another person”. More in conformity with the general approach adopted in Ewels and the specific application of the boni morestest in Bakkerud would be to insert the phrase “take reasonable steps to” before “eliminate that danger” in the quotation contained in the previous sentence. The facts of the present case are straightforward and not complicated by the presence of defences pertaining to the absence of wrongfulness or negligence . This makes it a good example to present to undergraduate students confronted for the first time by the intricacies of ascertaining the wrongfulness of an omission.